2007
DOI: 10.1002/dneu.20534
|View full text |Cite
|
Sign up to set email alerts
|

Differential enhancement of neural and photoreceptor cell differentiation of cultured pineal cells by FGF‐1, IGF‐1, and EGF

Abstract: There are several common features between the pineal organ and the lateral eye in their developmental and evolutionary aspects. The avian pineal is a photoendocrine organ that originates from the diencephalon roof and represents a transitional type between the photosensory organ of lower vertebrates and the endocrine gland of mammals. Previous cell culture studies have shown that embryonic avian pineal cells retain a wide spectrum of differentiative capacities, although little is known about the mechanisms inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Lawrence et al ( Lawrence et al, 2007 ) and Das et al ( Das et al, 2006 ) attempted to cultivate mammalian Müller cells using FGF2, retinoic acid (RA), and brain-derived neurotrophic factor (BDNF), which seemed to promote the regeneration of ganglia, bipolar cells, and photoreceptors. Some studies ( Araki et al, 2007 ) suggest that EGF can enhance the possibility of pineal cells differentiating into photoreceptor cells. However, the mechanisms that control the differentiation of mammalian Müller cell-derived progenitors in adult retina are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Lawrence et al ( Lawrence et al, 2007 ) and Das et al ( Das et al, 2006 ) attempted to cultivate mammalian Müller cells using FGF2, retinoic acid (RA), and brain-derived neurotrophic factor (BDNF), which seemed to promote the regeneration of ganglia, bipolar cells, and photoreceptors. Some studies ( Araki et al, 2007 ) suggest that EGF can enhance the possibility of pineal cells differentiating into photoreceptor cells. However, the mechanisms that control the differentiation of mammalian Müller cell-derived progenitors in adult retina are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Igf1r in the pineal gland has not been fully established; however, it has been suggested that cross-talk may exist between insulin and noradrenergic signaling (52). Also, Igf1 may influence differentiation of pineal cells (53). miRNAs may influence these process through effects on Igf1.…”
Section: Mirna Effects On the Pineal Glandmentioning
confidence: 99%